An empirical investigation of fund managers’ religiosity level during investment decisions - Jaiyeoba, Haruna Babatunde; Adewale, Abideen Adeyemi; Haron, Razali (2017)
This study investigates investors’ confidence in the Malaysian stock market based on the notion that stocks are the best investment avenue for long-term investors, who can just buy and hold through the ups and downs of the market. In addition, it also examines the role of investors’ religiosity during investment decisions. To achieve these objectives, survey questionnaire was developed by the researchers and completed by 366 stock market investors, including fund managers and retail investors. Using several suitable analyses, we have concluded, though with caution, that stock market investors have confidence in the Malaysian stock market as the best investment avenue in the country. Moreover, this study has also shown that highly religious investors hold firmly to their religion guidelines when making investment decisions compared to other investors in the lowest category; more so, ethical businesses and being socially responsible are other factors found important to the investors before selecting company for investment reasons. As a result, discussions are made, implications are offered, and recommendations for future studies are discussed.